KANDUNGAN SELULOSA DAN LIGNIN BERBAGAI SUMBER BAHAN ORGANIK SETELAH DEKOMPOSISI PADA TANAH LATOSOL - Saptiningsih, Endang (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2015)
Latosol soil is soil that experienced weathering characteristics further with acidic pH, organic matter content and low nutrient. Various sources of organic material such as straw, husks, leaves and waste of banana peel can be used as organic matter added to the soil to increase the cation exchange capacity and nutrient content of the soil. This study aims to determine the content of cellulose and lignin various sources of organic matter in the soil latosol after the source of organic material of straw, leaves, husks and banana peel waste. The study was conducted at the Laboratory of Structure and Function of Plants, State University of Diponegoro. Latosol soil taken from Mount Pati Semarang. A source of organic matter added to the soil latosol consists of four sources of organic matter as a treatment that straw, chaff, leaves and banana peels. Each treatment was given repeat 3 times. A source of organic matter and soil latosol incubated for 3 months so that the ongoing process of decomposition. Analyzed soil pH, organic matter content and cation exchange capacity. A source of organic matter was analyzed lignin and cellulose. The results showed straw and husks containing lignin and cellulose higher than the leaves and banana peels. Leaves and banana peels decompose more quickly than straw and chaff. Organic material with a low content of lignin and cellulose in the leaves and banana peels accelerate the decomposition process, so it will affect the cation exchange capacity and soil nutrient sorption. Â Keywords : Organic matter, latosol, decomposition